IbM KECAMATAN SUKARAJA MENUJU DESA MANDIRI ENERGI [IbM SUKARAJA DISTRICTS TOWARDS AN ENERGY INDEPENDENT VILLAGE] - Dikdik Mulyadi; Lela Mukmilah Y (Jurnal Sinergitas PKM & CSR, 2017)
Community service programs conducted in Sukamekar and Cisarua villages in Kecamatan Sukaraja has a theme "IbM Sukaraja Districts Towards an Energy Independent Village". The expected objective of the science and technology program for this community is to make the existing community in Sukaraja Sukabumi districts generally independent in the field of energy and particularly the villages of Sukamekar and Cisarua of Sukaraja Disticts. The method used by some stage of the electoral groups in each village based on the potential of cow dung waste, socialization biogas to a selected group, training and implementation of biogas installation and monitoring and evaluation of all activities conducted. The result of monitoring and evaluation of this activity shows that cow dung in Sukamekar and Cisarua villages of Sukaraja districts can be utilized to produce biogas that  used for cooking purposes IbM implementation provides some benefits in the field of economic, social, security and mastery of technology.